THE MACRO-REGION OF SOUTHERN ITALY: INTELLECTUAL SUGGESTION OR FEASIBLE WAY? - Claudio Novembre (Bollettino della Società Geografica Italiana)
The idea of a macro-region of Southern Italy is only an intellectual suggestion or could represent a viable option to treat a greater impact on the many wounds that plague this part of the country? And yet, if we imagine a macro-region of the South, it is more useful to think it is functional aggregation, oriented to the realization of joint projects, or even as a separate institutional expression of a clear political legitimacy? Analyze the feasibility of this idea that increasingly stands out as theme of confrontation between experts, politicians, bureaucrats and public administrators is the goal of this contribution. Contribution to that found in the most recent annual reports published by an institution as important as the SVIMEZ and by stimulating and provocative book by Giorgio Ruffolo 2010, A Country too Long, the foundations for a deeper reflection. If, as he wrote Giuseppe Mazzini, «Italy will be what will be the South», the precise analyzes that SVIMEZ has made in recent years give us a worrying photograph of state of health of the South and, by extension, of the entire peninsula. Hence the need to re-open a discussion to try to give a unitary dimension to the issue of the South, because the largest and most populous region in the Euro Area which still presents situations of serious under-utilization of local resources, needs strategic planning of vast dimensions given that, beyond the local differences, the problems remain unitary.